Leadership disputes as ongoing: an analysis of the Zion Apostolic Faith Mission church in Zimbabwe (1923). - Shangarai, Rabson (Midlands State University, 2017)
This dissertation seeks to show that leadership disputes are an ongoing phenomenon in the Zion Apostolic Faith Mission Church in Zimbabwe since its inception in 1923 to date. The founder Bishop faced some leadership disputes, his son and the second bishop Dorious (1985-2012) faced some leadership disputes. Dictatorship and general church maladministration during Dorious’ reign created leadership disputes which spilled into today’s leadership wrangle pitting Jameson the eldest surviving son of the late Bishop Dorious and his youngster Ezra. Factors precipitating these disputes shall be revealed in due course and a conclusion shall be available.